An artist's impression of Richardson's fantastic forecast factory1. (January 2016) - Lynch, Peter
Abstract : In 1922 Lewis Fry Richardson published a remarkable book, Weather Prediction by Numerical Process, describing his attempt to forecast changes in the weather by numerical means. In his preface, Richardson wrote: This investigation grew out of a study of finite differences and first took shape in 1911 as the fantasy … [described below] . Several artists have created images of the forecast factory. One particular image, which has recently come to light, is described in this note. The painting is a remarkable work, rich in detail and replete with hidden gems.